Association of angiotensin II and receptors in peri-implantation endometrium with microvessel density and pregnancy outcomes of women with recurrent implantation failure after embryo transfer - Qi, Ruofan; Zhang, Tao; Zhang, Yingying; Chung, Jacqueline Pui Wah; Yang, Wen-Jui; Wang, Chi Chiu (Frontiers in Endocrinology, 2023)
Purpose Investigate whether local angiotensin II (AngII) and its AngII type 1 and 2 receptors (AT1R, AT2R) in the endometrium are different and correlate with microvessel density in women with reproductive failure and pregnancy outcomes. Methods Endometrium during the window of implantation from 40 women with recurrent miscarriage (RM) and 40 with recurrent implantation failure (RIF) were compared with 27 fertile women. Peri-implantation endometrium from 54 women prior to euploid embryo transfer were collected and compared in women with successful pregnancy and unsuccessful pregnancy. Results Compared with fertile women, expression of AT2R was significantly lower, while AT1R/AT2R expression ratio was significantly higher in the stroma of the RIF group. Endometrium arteriole MVD was significantly lower and negatively correlated with the AT1R/AT2R expression ratio in the stroma of the RIF group. No significant differences and correlations were found in the RM group. Compared with the pregnancy group, expression of AT1R and AT2R were significantly lower in all compartments, but only AT1R/AT2R ratio was significantly higher in the stroma of the non-pregnancy group. Similarly, endometrium arteriole MVD was also significantly lower and negatively correlated with the AT1R/AT2R ratio in the stroma of the non-pregnancy group. Conclusion Local renin-angiotensin system is dysregulated in peri-implantation endometrium and associated with abnormal angiogenesis in RIF and poor implantation outcome after embryo transfer.